Protein aggregation, metals and oxidative stress in neurodegenerative diseases - Allsop, David (Henry Stewart Talks, 2007)
Introduction to protein conformational brain diseases, Alzheimer's disease, A-beta and tau, A-beta oligomers and toxicity, A-beta generates hydrogen peroxide, Results from experiments using electron spin resonance spectroscopy, Parkinson's disease, Generation of hydrogen peroxide from alpha synuclein, toxic fragments of the prion protein and the familial British dementia peptide, Early oligomers appear to generate hydrogen peroxide, Huntington's disease, Protein aggregates could be protective, Potential common toxic pathway for these brain diseases